IMPROVING THE METHOD OF ENDOSCOPIC REMOVAL OF SUPERFICIAL POLYPOID AND NON-POLYPOID FORMATIONS OF THE GASTROINTESTINAL TRACT (INTERNATIONAL CONFERENCE OF NATURAL AND SOCIAL-HUMANITARIAN SCIENCES, 2024)
Polyps occupy a special place in the general structure of diseases of the gastrointestinal tract. Depending on the location of the formation, a gastroscope or colonoscope is inserted and an examination of the area of interest is performed, the polyp is identified. A sterile gel is prepared, for which 1.0 g of the powdered HEMOBEN composition is mixed with 20 ml of 0.1% methylene blue solution with constant stirring for 1 minute. Thus, the developed method of endoscopic removal of superficial polypoid and non-polypoid neoplasms of the gastrointestinal tract is characterized by simplicity of execution.